Complementary Nursing Intervention of Acupressure and Bay Leaf Extract (Syzygium polyanthum) on Reducing Pain among Patients with Arthritis Gout - Nadia Sari; Tri Johan Agus Yuswanto; Diyah Fatmasari (Alta Dharma Publisher, 2020)
Arthritis Gout is a disease affecting the joints characterized. It was characteristic of monosodium urate monohydrate (MSU) accumulation in tissue synovial or other tissues. The prevalence of gouty arthritis in various countries in the world in the last few decades continues to increase. In patients, the main problem that occurs with gouty arthritis is pain and stiffness in the joints that recur, causing reddish swelling around the joints due to increased uric acid. Alternative treatment for arthritis gout in nursing interventions such as acupressure and bay leaf extract (Syzygium polyanthum). It could reduce and relieve pain in gout arthritis patients. This study examines the analysis of complementary nursing interventions of acupressure and bay leaf extract (Syzygium polyanthum) on pain in arthritis gout clients. This study used true experimental with approach pre-test and post-test control group design. Data collection involved 30 respondents with arthritis gout clients, selected through technique probability sampling with simple random sampling, divided into three groups. The intervention group received the therapy acupressure and bay leaf extract (Syzygium polyanthum). The first control group received the therapy acupressure, and the second control group received bay leaf extract therapy (Syzygium polyanthum). Pain intensity decreased in the intervention, control one, and managing two groups. But based on the One Way ANOVA test on the pain variable, it showed that the intervention group had the most significant reduction with a value (4.70±1.05) in the control group 1 (3.10±0.99) and control group 2 (3.0±1.05) with a significant p-value of 0.001 (<0.05). Conclusion giving complementary nursing intervention acupressure and bay leaf extract (Syzygium polyanthum) effectively reduces pain in arthritis gout patients